Step-by-step explanation:
![=> 2 {x}^{2} + \frac{7}{2}x + \frac{3}{4} = 0](https://tex.z-dn.net/?f=%20%3D%3E%20%202%20%7Bx%7D%5E%7B2%7D%20%20%2B%20%20%5Cfrac%7B7%7D%7B2%7Dx%20%2B%20%20%5Cfrac%7B3%7D%7B4%7D%20%20%3D%200)
![=> \frac{8 {x}^{2} + 14x + 3}{4} = 0](https://tex.z-dn.net/?f=%20%3D%3E%20%5Cfrac%7B8%20%7Bx%7D%5E%7B2%7D%20%20%2B%2014x%20%2B%203%7D%7B4%7D%20%3D%200%20)
![=> 8 {x}^{2} + 14x + 3 = 0](https://tex.z-dn.net/?f=%20%3D%3E%208%20%7Bx%7D%5E%7B2%7D%20%20%2B%2014x%20%2B%203%20%3D%200)
![=> 8 {x}^{2} + 12x + 2x + 3 = 0](https://tex.z-dn.net/?f=%20%3D%3E%208%20%7Bx%7D%5E%7B2%7D%20%20%2B%2012x%20%2B%202x%20%2B%203%20%3D%200)
![=> 4x(2x + 3) + 1(2x + 3) = 0](https://tex.z-dn.net/?f=%20%3D%3E%204x%282x%20%2B%203%29%20%2B%201%282x%20%2B%203%29%20%3D%200)
![= > (2x + 3)(4x + 1) = 0](https://tex.z-dn.net/?f=%20%3D%20%3E%20%282x%20%2B%203%29%284x%20%2B%201%29%20%3D%200)
![= > x = - \frac{3}{2} or \frac{ - 1}{4}](https://tex.z-dn.net/?f=%20%3D%20%20%3E%20x%20%3D%20%20-%20%20%5Cfrac%7B3%7D%7B2%7D%20or%20%5Cfrac%7B%20-%201%7D%7B4%7D%20)
option C
Answer: D
Explanation: rad 36 is the same as rad 6^2 and they are perfect roots do then you just add the numbers like usual.
Answer:
-19
Step-by-step explanation:
ok so since they give you all the variables you can substitute their values
for example instead of 3xy you can write 3*(-4)y
so that is the basic idea for this problem
after substituting, the new equation is 3*(-4)*2 +5
i plan on using order of operations, or PEMDAS
3*(-4)=(-12)
(-12)*2=(-24)
-24+5=-19
so the answer is -19
hope this helps!
Answer:
it Doesnt have a square root
Step-by-step explanation:
we are given equation as
![y=x^2](https://tex.z-dn.net/?f=%20y%3Dx%5E2%20)
so, when we replace x as x+7
our graph will shift left side by 7 units
![y=(x+7)^2](https://tex.z-dn.net/?f=%20y%3D%28x%2B7%29%5E2%20)
we can see the graph